CSharp and the .NET Platform 2nd Edition - Troelsen, Andrew (Apress, 2012)
I remember a time years ago when I proposed a book to Apress regarding a forthcoming software SDK named Next Generation Windows Services (NGWS). As you may already know, NGWS eventually became what we now know as the .NET platform. My research of the C# programming language and the .NET platform took place in parallel with the authoring of the text. It was a fantastic project; however, I must confess that it was more than a bit nerve-wracking writing about a technology that was undergoing drastic changes over the course of its development. It pains me to recall how many chapters had to be completely destroyed and rewritten during that time. Thankfully, after many sleepless nights, the first edition of C# and the .NET Platform was published in con-junction with the release of .NET Beta 2, circa the summer of 2001. Since that point, I have been extremely happy and grateful to see that the first edition of this text was very well received by the press and, most importantly, the readers. Over the years, it was nominated as a Jolt award finalist (I lost ... crap!) as well as the 2003 Referenceware programming book of the year (I won ... cool!). Although the first edition of this book has enjoyed a good run, it became clear that a second edition was in order—not only to account for the changes brought about with the minor release of the .NET platform, but to expand upon and improve the existing content. As I write this frontmatter, version 1.1 of the .NET platform is just about official, and I am happy to say that C# and the .NET Platform, Second Edition is being released in tandem.